Microbiological Effects of Periodontal Therapy Plus Azithromycin in Patients with Diabetes: Results from a Randomized Clinical Trial (2014)
ABSTRACT: Current evidence suggests that periodontal infection may aggravate diabetes control. The aim of this study was to determine the changes in the frequency with which Porphyromonas gingivalis, Tannerella forsythia, Treponema denticola and Aggregatibacter actinomycetemcomitans were detected in patients with diabetes with the use of non-surgical therapy plus azithromycin in a randomized clinical trial. One hundred and five (105) patients with diabetes and chronic periodontitis were randomly assigned to three treatment groups: subgingival mechanical therapy with azithromycin, subgingival mechanical therapy with placebo and supragingival prophylaxis with azithromycin. Complete periodontal clinical examinations and detection of periodontal pathogens using polymerase chain reaction were carried out at baseline, 3, 6 and 9 months after periodontal therapy. The frequency with which Porphyromonas gingivalis, Treponemadenticola and Aggregatibacter actinomycetemcomitans were detected decreased at 3 months in all groups. Tannerella forsythia increased after3 months in all groups. All organisms had similar frequencies at 9 months in all groups. Subgingival mechanical therapy with adjunctive azithromycin had no additional effect on the frequency with which the periodontal pathogens investigated were detected in patients with diabetes.